Developing nano-bonded refractory castables with enhanced green mechanical properties. Issue 2 (March 2015) - Nouri-Khezrabad, M.; Luz, A.P.; Salvini, V.R.; Golestani-Fard, F.; Rezaie, H.R.; Pandolfelli, V.C.
Abstract: Applying colloidal silica suspensions as a binder source for refractory castables has been of great interest in recent years. Nevertheless, the resultant low green mechanical strength of these castables has hindered their application in relevant areas. The current paper provides a novel engineering route to improve the mechanical properties of colloidal silica bonded castables before firing. In order to attain this target, small amounts of calcium aluminate cement (CAC) and/or hydratable alumina (HA) were used as gelling agents. A splitting tensile test showed that although using HA resulted in a more significant increase in the modulus of rupture of the samples when compared to CAC, mixing both (CAC+HA) had the most positive impact on the green mechanical properties of the castables, leading to strength levels as high as the reference cement-bonded system (CAC-Ref). XRD and DTG tests were carried out to evaluate the hydration behavior of the selected additives. The results indicated that CAC enhanced the hydration of HA based on the accelerated dissolution of the gel layer formed on HA particles, which was induced by the Al(OH)4 − common ion effect. The proposed mechanism was confirmed by a specific conductivity test. Additionally, 29 Si solid state NMR spectroscopy was used to determine the effect of the dual additive system (HA+CAC) on the siloxane bond formation. Quantification of Q 2, Q 3 and Q 4 species in alumina–colloidal silica suspensions containing HA, CAC or HA+CAC highlighted that the improved green strength is mainly related to a more effective hydration of HA. Based on the NMR and XHR SEM analyses, HA can be considered as an alternative gelling agent for nano-bonded refractory castables.